EEG source analysis and fMRI reveal two electrical sources in the fronto-parietal operculum during subepidermal finger stimulation - Stancák, Andrej; Polácek, Hubert; Vrána, Jirí; Rachmanová, Rosa; Hoechstetter, Karsten; Tintra, Jaroslav; Scherg, Michael (NeuroImage, 2005)
Using functional magnetic resonance imaging (fMRI) and electroencephalographic (EEG) source dipole analysis in 10 normal subjects, two electrical source dipoles in the contralateral fronto-parietal operculum were identified during repetitive painful subepidermal stimulation of the right index finger. The anterior source dipole peaking at 79 +/- 8 ms (mean +/- SD) was located in the frontal operculum, and oriented tangentially toward the cortical surface. The posterior source dipole peaking at 118 +/- 12 ms was located in the upper bank of the Sylvian fissure corresponding to the second somatosensory cortex (S2). The orientations of the posterior source dipoles displayed large variability, but differed significantly (P < 0.05) from the orientations of the anterior source dipoles. Electrical sources and fMRI clusters were also observed in ipsilateral fronto-parietal operculum. However, due to low signal-to-noise ratio of ipsilateral EEG sources in individual recordings, separation of sources into anterior and posterior clusters was not performed. Combined fMRI and source dipole EEG analysis of individual data suggests the presence of two distinct electrical sources in the fronto-parietal operculum participating in processing of somatosensory stimuli. The anterior region of the fronto-parietal operculum shows earlier peak activation than the posterior region.
Keywords: Pain Threshold; aquaeductus cerebri; mapování mozku; mužské pohlaví; Male; dominance mozková; somatosenzorické korové centrum; Electric Stimulation; čelní lalok; Humans; Image Processing, Computer-Assisted; elektroencefalografie; Skin; kůže; Arousal; Imaging, Three-Dimensional; Frontal Lobe; somatosenzorické evokované potenciály; počítačové zpracování obrazu; magnetická rezonanční tomografie; elektrická stimulace; Somatosensory Cortex; lidé; Fingers; Evoked Potentials, Somatosensory; Parietal Lobe; reakční čas; Cerebral Aqueduct; Magnetic Resonance Imaging; Electroencephalography; práh bolesti; Brain Mapping; prsty ruky; dospělí; Adult; zobrazování trojrozměrné; arousal; temenní lalok; Dominance, Cerebral; Reaction Time